Association between respiratory disease pathogens in calves near feedlot arrival with treatment for bovine respiratory disease and subsequent antimicrobial resistance status - Abi Younes, Jennifer N.; Campbell, John R.; Gow, Sheryl P.; Woolums, Amelia R.; Waldner, Cheryl L. (Frontiers in Veterinary Science, 2024)
Introduction: This study assessed the risk of first treatment for bovine respiratory disease (BRD) given detection of nasopharyngeal bacteria (Mannheimia haemolytica, Pasteurella multocida, and Histophilus somni) and corresponding likelihood of antimicrobial susceptibility (C/S) at two time points during the early feeding period. Relationships between C/S results and later treatment for BRD were evaluated at both the calf-level and pen-level. The association between calf-level and pen-level C/S findings during the early feeding period and subsequent C/S results at BRD treatment were also reported. Methods: Auction-sourced, recently-weaned beef calves (n=1,599 steers) were placed in adjacent feedlot pens (8 x 100 calves) in two subsequent years. Deep nasopharyngeal (DNP) swabs were collected from all calves at time of arrival processing (1DOF) and before metaphylaxis administration with either tulathromycin or oxytetracycline, 12 days later (13DOF), and at the time of first treatment for BRD. All samples were tested for C/S. Results: Several pen-level and individual calf-level C/S measures of interest were associated with risk of future treatment for BRD and C/S at the time of treatment. The median DOF for first BRD treatment was 24 days following tulathromycin metaphylaxis and 11 days following oxytetracycline. Overall, sampling at 13DOF resulted in the best fit for more models of subsequent treatment for BRD and C/S results at BRD treatment than for sampling at arrival. In individual calves, recovery of M. haemolytica, P. multocida, or H. somni at 13DOF was associated with subsequent treatment for BRD within 45DOF. Pen-level prevalence of Pasteurellacea bacteria with tetracycline or macrolide resistance at arrival and 13DOF were associated with detection of bacteria with antimicrobial resistance (AMR) at BRD treatment, as were individual calf results at 13DOF. Discussion: These findings suggest that the bacteria and AMR outcomes recovered from cattle near two weeks on feed can inform the prediction of future BRD risk and concurrent antimicrobial susceptibility results at time of first BRD treatment. Notably, the associations between pen-level C/S results from previous testing and corresponding findings in calves with BRD from the same pen suggested potential testing strategies to inform antimicrobial use protocols for feedlot cattle.